Análise físico-química do húmus obtido por vermicompostagem em diferentes alimentações da espécie Eisenia andrei - Sakakibara, Jun (2021)
Brazil faces a major problem regarding the management of solid waste, an aggravating factor being the amount of solid waste disposal that can be treated. The application of vermicomposting to various finished residues, besides reducing the disposal of organic waste to landfills, produces a compound with high added value for its excellent fertilizing properties and not harmful to the environment: the earthworm humus. The efficiency of this technique even allows to evaluate the composting of new residues, as depleted substrate from mushroom cultivation. The variation in the feeding of earthworms followed by the analysis of the generated humus allows to verify the possible variations of the resulting compound, including analyzing its possible commercial properties. The extraction of liquid humus allows a deeper analysis of the compost with regard to the amounts of humic substances in the product, since it highlights the soluble fractions involved in the composting process.